Foreign investments as a form of enterprise strategy: On the results of a survey - Gunter Kayser; Uwe Schwarting (Intereconomics, 1981)
During the course of 1980 West German enterprises and private persons were responsible for approximately DM 8.16 bn in foreign investments. The sum total of German foreign investments has now reached a level of DM 74.2 bn. Both these figures indicate the increasing internationalisation of the German economy, at the same time suggesting that a considerable wealth of experience has been acquired by German firms already resident abroad, which could facilitate entry into foreign markets for possible investors. With this in mind a survey of German subsidiary companies in 17 countries was carried out, the aim of which was to obtain close to the market information on the problems, conditions and background details entailed in any particular undertaking abroad.
Keywords: 330